2016
DOI: 10.18632/oncotarget.12591
|View full text |Cite
|
Sign up to set email alerts
|

Association of transcription factor 7-like 2 gene polymorphisms with breast cancer risk in northwest Chinese women

Abstract: Genetic variations in transcription factor 7-like 2 (TCF7L2) are associated with cancer risk. This study was conducted to establish the relationship between TCF7L2 polymorphisms (rs1225404, rs7003146, and rs7903146) and clinical features and risk of breast cancer in Northwest Chinese Han women. In this study, three polymorphisms of TCF7L2 (rs1225404, rs7003146, and rs7903146) were genotyped in 458 patients with breast cancer and 500 healthy controls using the Sequenom MassARRAY-iPLEX system. We evaluated the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Another research showed a significant correlation between rs7003146 (G/T) polymorphism and reduction of BC risk in Chinese Han population [ 20 ], and rs1225404 (GA/AA genotype) was a probable anti-breast cancer factor in Hispanic population [ 15 ]. Till now, limited study focused on correlation between TCF7L2 gene SNPs and BC risk, while just one study [ 21 ] was performed in Chinese population. Rs7903146 is located at TCF7L2 intron region and is associated with an increased risk of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Another research showed a significant correlation between rs7003146 (G/T) polymorphism and reduction of BC risk in Chinese Han population [ 20 ], and rs1225404 (GA/AA genotype) was a probable anti-breast cancer factor in Hispanic population [ 15 ]. Till now, limited study focused on correlation between TCF7L2 gene SNPs and BC risk, while just one study [ 21 ] was performed in Chinese population. Rs7903146 is located at TCF7L2 intron region and is associated with an increased risk of BC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that the most frequent TCF7L2 variants (rs7903146, intron 3 and rs12255372, intron 4) affect the mRNA stability and the alternative splicing (24,26). Specifically, in breast cancer, these TCF7L2 variants (rs12255372 and rs7903146) shown results contradictories regards to cancer susceptibility (21,29,(31)(32)(33)(34)41). In this study, we found an association of the genotypes CT and TT of both variants with breast cancer risk.…”
Section: Discussionmentioning
confidence: 43%
“…Specifically, the AXIN2 rs2240308 (C > T) variant has been assessed and associated with several cancers (15)(16)(17)(18)(19)(20); for breast cancer, this variant have been studied only in two different populations, although with inconsistent results (20,22). For the variants rs7903146 (C > T) and rs12255372 (G > T) of the TCF7L2 gene, various studies have been conducted in colorectal (24)(25)(26)(27)(28), prostate (29), lung (30), and breast cancer (31)(32)(33)(34). In breast cancer, these variants show contradictory results among different populations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, epidemiological studies have shown that TCF7L2 gene polymorphisms are associated with increased susceptibility to carcinomas, including of the breast (35,36). Additionally, TCF7L2 can increase the expression of genes involved in the proliferation, apoptosis, invasion and metastasis of tumor cells (37,38). TCF7L2 synthesis is directly regulated by miR-21 transcription (39).…”
Section: Discussionmentioning
confidence: 99%